(E)-1-[1-(3-Chlorophenyl)ethylidene]-2-(2,4-dinitrophenyl)hydrazine - Fun, Hoong-Kun (International Union of Crystallography, 2012)
There are two crystallographically independent molecules in the asymmetric unit of the title compound, C(14)H(11)ClN(4)O(4), with the same E conformation about the C=N double bond. The molecules are approximately planar, with a dihedral angle between the benzene rings of 10.24 (12)° in one molecule and 4.73 (12)° in the other. In both molecules, the ortho-nitro groups of the 2,4-dinitrophenyl units are coplanar to their bound benzene rings, whereas the para-nitro groups are slightly twisted. In each molecule, intramolecular N—H⋯O hydrogen bonds generate S(6) ring motifs. In the crystal, molecules are linked by weak C—H⋯O interactions into sheets parallel to the (-102) plane. These sheets are stacked by π–π interactions, with centroid–centroid distances of 3.7008 (14) and 3.7459 (14) Å. A Cl⋯O short contact [3.111 (2) Å] is observed.